Transcranial electrical and magnetic stimulation (tES and TMS) for addiction medicine: A consensus paper on the present state of the science and the road ahead. (September 2019) - Ekhtiari, Hamed; Tavakoli, Hosna; Addolorato, Giovanni; Baeken, Chris; Bonci, Antonello; Campanella, Salvatore; Castelo-Branco, Luis; Challet-Bouju, Gaëlle; Clark, Vincent P.; Claus, Eric; Dannon, Pinhas N.; Del Felice, Alessandra; et al.
Highlights: This is an overview of the state of tES/TMS applied in drug addictions. Neuroscience will be translated into tES/TMS tools for clinical practice in addiction. Heterogeneity of methods and outcome measures in the literature are addressed. This article provides guidelines for best practices in tES/TMS addiction research. Abstract: There is growing interest in non-invasive brain stimulation (NIBS) as a novel treatment option for substance-use disorders (SUDs). Recent momentum stems from a foundation of preclinical neuroscience demonstrating links between neural circuits and drug consuming behavior, as well as recent FDA-approval of NIBS treatments for mental health disorders that share overlapping pathology with SUDs. As with any emerging field, enthusiasm must be tempered by reason; lessons learned from the past should be prudently applied to future therapies. Here, an international ensemble of experts provides an overview of the state of transcranial-electrical (tES) and transcranial-magnetic (TMS) stimulation applied in SUDs. This consensus paper provides a systematic literature review on published data – emphasizing the heterogeneity of methods and outcome measures while suggesting strategies to help bridge knowledge gaps. The goal of this effort is to provide the community with guidelines for best practices in tES/TMS SUD research. We hope this will accelerate the speed at which the community translates basic neuroscience into advanced neuromodulation tools for clinical practice in addiction medicine.